Expanded description & range extension of Lycodon sidiki Wostl, Hamidy, Kurniawan & Smith, 2017 (Squamata: Colubridae) - Nguyen, Tan Van; David, Patrick; Vogel, Gernot (Zootaxa, 2024)
The wolf snake species Lycodon sidiki was described based on only one specimen from Aceh Province, Sumatra, Indonesia. Herein, we report new characters and a range extension of this species based on a re-examination of eight preserved specimens deposited in the collections of the Naturhistorisches Museum Wien, Austria (NHMW). Based on the new information, we record this species for the first time from West Sumatra Province (Padang) and update its diagnostic characters. Furthermore, we provide distinguishing features from the closely related species belonging to the Lycodon fasciatus species group. In addition, we also update the key to Lycodon species in Sumatra Island.